Intravenous Ketamine for Suicidal Behavior in Severe Depression with Psychotic Features - T. V. Pavan Kumar; Divya Bolla; Raj Kiran Donthu; Anzory Pathak (Annals of Indian Psychiatry)
Depression is the leading cause of suicide, and antidepressants and modified electroconvulsive therapy (mECT) are the preferred treatment modalities. Ketamine is an established anesthetic agent and evidence for its use in depression is evolving. Here, we discuss the experience of treating severe depression with intravenous (IV) ketamine. A patient in his mid-forties presented with a 2-month history of pervasive low mood, altered biological functions, decreased interest, and suspiciousness and was diagnosed with severe depression with psychotic features and suicidal ideas. As per the guidelines, started on antidepressants and planned for mECT. As the patient and family members were not willing for mECT, based on evidence, IV ketamine was discussed and started. Over six sessions of IV ketamine, there was significant improvement in both objective rating scores and clinically. IV ketamine can be a good adjunctive in the treatment of severe depression with suicidal ideas but needs to be backed up by robust studies.